An investigation of fatigue among Jordanian nurses based on their gender measured using the OFER 15: a primary quantitative study - Al-Masaeed, Mahmoud; Rasdi, Irniza; Paul O’Brien, Anthony; Alqudah, Muhammad; Guilhermino, Michelle (Izdatel'stvo Elm, 2023)
This study aims to investigate the levels of fatigue among Jordanian nurses. Also, investigate the impact of the nurses' socio-demographic variables on their fatigue levels. Data was collected from a sample of two hospitals in Jordan using a simple random sampling technique. The study was developed through collecting primary quantitative data. Data was collected through closed-ended questionnaires based on the OFER 15 tool as a basis for measuring fatigue. The findings relied on a total of 517 respondents (154 male and 363 female). This was an equitable representation of both genders in the Jordan nurses' workforce. The socio-demographics showed no significant variance among genders apart from smoking and marital status. Using the OFER 15 tools manual and scoring, the findings established a high chronic (Female =90.67, Male = 76.72) and acute (Female=77.56, Male =74.74) fatigue for female nurses as compared to their male peers. Significant correlations were found between the three types of OFER 15 scores (chronic, acute, and inter-shift-recovery) and five independent variables; Age (chronic), Gender (acute and inter-shift), education level (inter-shift recovery), Marital status (acute fatigue) number of dependents (chronic fatigue) and the weekly working hours (chronic fatigue) levels, respectively. On gender differences, it established that female nurses had a higher chronic and acute fatigue than male peers. However, they also had a higher inter-shift recovery index than the male nurses. There is a high fatigue prevalence among Jordanian nurses. There is an urgent need to address acute and chronic fatigue types as a matter of priority. Providing better resting areas and exercise programs for nurses is highly recommended.